Some apects of economic development with special reference to East Africa - Oloya, J. J. (Nairobi East African Literature Bureau, 1968)
Includes topics that cover: economic development-East Africa; general character of the East African economy; marketing, agricultural efficiency; and industrialisation.
lje 20/09/2018
Loans
Keywords: Economic development; Marketing; Agriculture; Industrialisation; East Africa